Panamarenko - Theys, Hans; Stroop, J.S. (Montagne de miel : [s.n.], 1992)
Panamarenko should be considered one of the main artists of our century. After having hit the public at the Wide White Space Gallery (Antwerp, Belgium) in 1966, he got befriended with Joseph Beuys, who introduced him in Germany in 1968, organizing an exhibition of Das Flugzeug at the Academy of Düsseldorf. From that moment on, Panamarenko remained one of the most important, but least seizable figures on the European art scene. At last, a readable book, providing 500 colour illustrations and a complete survey of his works, enables accurate insight in his intentions and realizations. Hans Theys, Montagne de Miel, 1992
ind. tent. p. 264-265, gr. tent. p. 268-273, bibliog. p. 277-281, biog. p. 283
Engels & Nederlands & Frans
boek
Keywords: Panamarenko